2007
DOI: 10.1002/jso.20928
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of various reconstructions employed after total gastrectomy

Abstract: Methods of restoring continuity after total gastrectomy, particularly those creating a "reservoir," have led to many publications over the last 20 years. These publications are herein reviewed in an attempt to answer questions regarding the clinical value of a jejunal "reservoir". The conclusion we reached from this review was that such a reconstruction does reduce unpleasant symptoms, aids weight maintenance, and is a valuable operative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
0
15
0
5
Order By: Relevance
“…Comparison between JPI-T and JPRY-T also begs the question of whether the passage of ingested content through the duodenum is important to maximize patients’ QOL. Two review papers concluded that this ‘duodenal passage’ was not associated with improvement in postoperative QOL [46, 47]. …”
Section: Discussionmentioning
confidence: 99%
“…Comparison between JPI-T and JPRY-T also begs the question of whether the passage of ingested content through the duodenum is important to maximize patients’ QOL. Two review papers concluded that this ‘duodenal passage’ was not associated with improvement in postoperative QOL [46, 47]. …”
Section: Discussionmentioning
confidence: 99%
“…Are cited: dumping in about 2% to 8%, diarrhea and malabsorption in 3% to 10%. Recurrence of cancer at the esophagus-jejunal anastomosis, because inadequate surgical margins is reported to occur in 1% to 4% of cases 3,4,6,19,28,31 . The overall mortality of total gastrectomy for gastric cancer ranges from 2% to 15%, secondary to surgery, and up to 20% if included other complications not directly related to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Other early complications such as abscesses, pneumonia, pulmonary embolism and thrombosis, and urinary tract infections are also present. In most cases, aggressive measures should be taken, such as treatment in the intensive care unit, drainage, relaparotomy, wide spectrum antibiotic therapy and nutritional support 3,8,13 . Recent randomized trials show no significant differences if the esophageal-jejunal anastomosis is manual or mechanical, since that the procedure is well made and indicated following well-established technical principles 13,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of these procedures use the small intestines [6]. Those using the colon (ileocecal juncture) are briefly exposed in this update but have not been studied in humans by controlled studies and are potentially fraught with the risk of additional complications (fistula, microbial pullulation) [7].…”
Section: Introductionmentioning
confidence: 99%